Clinical outcomes and treatment necessity in patients with toxin-negative Clostridioides difficile stool samples - Dae Hyeon Cho; Si-Ho Kim; Cheon Hoo Jeon; Hyoung Tae Kim; Kyoung-Jin Park; Junyoung Kim; Jiyeong Kwak; Byung Soo Kwan; Sungmin Kong; Jung Won Lee; Kwang Min Kim; Yu Mi Wi (BMC, 2024)
Abstract Purpose The clinical significance of negative toxin enzyme immunoassays (EIA) for Clostridioides difficile infections (CDIs) is unclear. Our study aimed to investigate the significance of toxin EIA-negative in the diagnosis and prognosis of CDI. Methods All stool specimens submitted for C. difficile toxin EIA testing were cultured to isolate C. difficile. In-house PCR for tcdA, tcdB, cdtA, and cdtB genes were performed using C. difficile isolates. Stool specimens were tested with C. difficile toxins A and B using EIA kit (RIDASCREEN Clostridium difficile toxin A/B, R-Biopharm AG, Darmstadt, Germany). Characteristics and subsequent CDI episodes of toxin EIA-negative and -positive patients were compared. Results Among 190 C. difficile PCR-positive patients, 83 (43.7%) were toxin EIA-negative. Multivariate analysis revealed independent associations toxin EIA-negative results and shorter hospital stays (OR = 0.98, 95% CI 0.96-0.99, p = 0.013) and less high-risk antibiotic exposure in the preceding month (OR = 0.38, 95% CI 0.16-0.94, p = 0.035). Toxin EIA-negative patients displayed a significantly lower white blood cell count rate (11.0 vs. 35.4%, p < 0.001). Among the 54 patients who were toxin EIA-negative and did not receive CDI treatment, three (5.6%) were diagnosed with CDI after 7-21 days without complication. Conclusion Our study demonstrates that toxin EIA-negative patients had milder laboratory findings and no complications, despite not receiving treatment. Prolonged hospitalisation and exposure to high-risk antibiotics could potentially serve as markers for the development of toxin EIA-positive CDI.